The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1021/acsnano.5b02322
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial B-Graphene: Large-Scale Growth and Atomic Structure

Abstract: Embedding foreign atoms or molecules in graphene has become the key approach in its functionalization and is intensively used for tuning its structural and electronic properties.Here, we present an efficient method based on chemical vapor deposition for large scale growth of boron-doped graphene (B-graphene) on Ni(111) and Co(0001) substrates using carborane molecules as the precursor. It is shown that up to 19 at. % of boron can be embedded in the graphene matrix and that a planar CÀB sp 2 network is formed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 42 publications
(89 reference statements)
8
36
0
Order By: Relevance
“…The angular dependence in the C K-edge NEXAFS spectra in Fig. 3a is similar to that of the pristine graphene (shown in Supplementary Figure 13a and Supplementary Note VIII ), indicating that the crystalline quality is preserved after doping with dilute heteroatoms 42 , 43 . Moreover, the B and N K-edge NEXAFS spectra are similar to the C K-edge NEXAFS spectra showing the 1s → π * and 1s → σ * transitions (Supplementary Figures 13b–e and Supplementary Note VIII ).…”
Section: Resultssupporting
confidence: 57%
“…The angular dependence in the C K-edge NEXAFS spectra in Fig. 3a is similar to that of the pristine graphene (shown in Supplementary Figure 13a and Supplementary Note VIII ), indicating that the crystalline quality is preserved after doping with dilute heteroatoms 42 , 43 . Moreover, the B and N K-edge NEXAFS spectra are similar to the C K-edge NEXAFS spectra showing the 1s → π * and 1s → σ * transitions (Supplementary Figures 13b–e and Supplementary Note VIII ).…”
Section: Resultssupporting
confidence: 57%
“…Its band structure has been comprehensively investigated as a function of the metal substrate by ARPES. It has been found that some metals interact so strongly with graphene that they cause a drastic change in its band structure [ 32 , 35 , 36 , 37 ], while others are considered weakly interacting and graphene placed on them is considered quasi-freestanding [ 32 , 33 , 38 ]. To change the graphene/substrate interaction a methodology, called intercalation, has been developed to allow the exchange of the graphene support.…”
Section: Spatially Resolved Arpes For 2d Materialsmentioning
confidence: 99%
“…2D B-doped graphene produced by CVD has been widely investigated. [48,118,119] However, 3D B-doped graphene fabricated by CVD has been rarely reported. According to our understanding, only one report exists of a work wherein Xue et al obtained 3D B-doped graphene for the first time by template-assisted CVD in conjunction with B and N codoping (which will be discussed later in Section 2.2.1).…”
Section: Boron-doped 3d Graphenementioning
confidence: 99%